Transverse Thermoelectric Conversion in the Mixed-Dimensional Semimetal WSi_{2} - Shoya Ohsumi; Yoshiki J. Sato; Ryuji Okazaki (PRX Energy)
Materials with axis-dependent conduction polarity are known as p×n-type or goniopolar conductors that can be used for transverse thermoelectric devices, allowing the longitudinal thermal current to be converted into the transverse electrical current. Here, we have performed experimental and computational studies on the transport properties of WSi_{2} single crystals, in which such axis-dependent conduction polarity of the thermopower and the Hall coefficient have recently been reported, and demonstrated the transverse thermoelectric effect by applying the temperature gradient in a direction rotated 45^{∘} from the crystallographic axis. We have observed strongly sample-dependent transport properties, which have also been observed in previous studies, and together with first-principles calculations we show that such sample-dependent transport properties originate from the band-dependent scattering rates of carriers. The calculated band-resolved Peltier conductivity shows that the mixed-dimensional electronic structure consisting of a quasi-one-dimensional electron Fermi surface and a quasi-two-dimensional hole surface is a key property for the axis-dependent conduction polarity. The directly obtained transverse thermoelectric figure of merit is comparable to that of the anomalous Nernst materials, implying that the present material is a potential candidate for transverse thermoelectric conversion.